The Meaning of the Phrase lādaʿat ṭôb wārāʿ in Genesis 3:22 : An Exegetical and Theological Study - Gosal, Fellix; Koapaha, Bouwmans Dandi (12th International Scholars Conference 2025, 2026)
Genesis chapter 3 recounts a pivotal event that altered the destiny of humankind—the fall of humanity into sin. One of the key elements in this narrative is the Hebrew phrase לָדַעַת טוֹב וָרָע (lādaʿat ṭôb wārāʿ), which appears in Genesis 3:22. Often translated as “to know good and evil,” this seemingly simple yet deeply enigmatic phrase marks a critical turning point for humanity in the Garden of Eden. This study explores the meaning of the phrase through a qualitative approach grounded in the Historical-Grammatical Method, analyzing the Hebrew text and examining related theological themes. The findings suggest that לָדַעַת טוֹב וָרָע refers to the knowledge and moral capacity to distinguish between good and evil—not merely recognizing the difference, but also possessing the ability to choose what is good over what is evil. According to this interpretation, the original human condition reflected God's own capacity for moral discernment, a capacity that was lost through transgression. This study contributes to Old Testament scholarship by offering a nuanced exegetical and theological analysis of Genesis 3:22, clarifying the phrase as moral discernment grounded in divine dependence—a finding that holds theological and pastoral significance, with implications for understanding human nature, sin, and ethical responsibility, and with potential impact on biblical interpretation, theological education, and spiritual formation.